Pengaruh Kepribadian Conscientiousness terhadap Kepuasan Perkawinan pada Istri yang Bekerja - Amarilys Andaritidya; Nandine Dwi Santika (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
Marital satisfaction greatly determines the domestic condition of each couple, both for a husband and a wife. Currently, many wives choose the path to become a career woman in order to fulfill their self-identity and economic independence which makes wives have many roles, such as being a housewife, mother of a child, and career woman. Personality contributes to marital satisfaction. This study aims to determine the influence of conscientiousness personality on marital satisfaction in working wives. Marital satisfaction was measured using the ENRICH Marital Satisfaction Scale (EMS) and personality conscientiousness was measured using the big five personalities that have been translated into Indonesian. This study uses a quantitative method with a research sample, namely the wife who works with. The sampling technique used is purposive sampling with sample criteria, namely wives who have worked for at least 1 year and live under the same roof with their husbands. The results showed that there was an influence of conscientiousness personality on marital satisfaction and the contribution of the influence of conscientiousness personality on marital satisfaction was 8.7%. Marital satisfaction in the respondents of this study is that working wives are in the high category.